2021
DOI: 10.1111/cge.14001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory factors, genetic variants, and predisposition for preterm birth

Abstract: Preterm birth is a major clinical and public health challenge, with a prevalence of 11% worldwide. It is the leading cause of death in children younger than 5 years old and represents 70% of neonatal deaths and 75% of neonatal morbidity. Despite the clinical and public health significance, this condition's etiology is still unclear, and most of the cases are spontaneous. There are several known preterm birth risk factors, including inflammatory diseases and the genetic background, although the underlying molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 142 publications
1
25
0
1
Order By: Relevance
“…Thus, the DECs derived from the above genes might mediate the essential processes of ECM remodeling and collagen degradation in PTB. Since it is generally accepted that pro-inflammatory responses and immune tolerance breaking are the important causes of fetal membrane damage and rupture, uterine contractions, and cervical changes, thus resulting in the occurrence of PTB, we speculated that the DECs in the chorion might regulate inflammatory processes in the development of PTB (83)(84)(85)(86). The evidence was provided by the target miRNAs and coexpressed mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the DECs derived from the above genes might mediate the essential processes of ECM remodeling and collagen degradation in PTB. Since it is generally accepted that pro-inflammatory responses and immune tolerance breaking are the important causes of fetal membrane damage and rupture, uterine contractions, and cervical changes, thus resulting in the occurrence of PTB, we speculated that the DECs in the chorion might regulate inflammatory processes in the development of PTB (83)(84)(85)(86). The evidence was provided by the target miRNAs and coexpressed mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…It had MAF of 0.164 in the CEU population (1000Genomes). The associations between TNF-308 haplotypes and the susceptibility to gestational diabetes mellitus, coronary artery disease, rheumatoid arthritis have been described [24][25][26][27][28][29]. The association of the rs1800629 variant with affected gene expression was initially discovered in previous studies [30].…”
Section: Selection Of Snps Genotyped In This Studymentioning
confidence: 99%
“…PTB has become a global public health issue, with mounting evidence indicating a syndrome attributed to various pathological processes ( 5 ). Many studies have revealed that genetic variations in pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1α (IL-1α) are associated with an increased risk of PTB ( 6 ). However, the relationship between genetic polymorphisms in anti-inflammatory cytokines and PTB risk remains controversial.…”
Section: Introductionmentioning
confidence: 99%